Check-in Phone Calls Six Weeks and Six Months After Musculoskeletal Specialty Care. (September 2021) - Mercado, Amelia E; Gonzalez, Amanda; Ring, David; Koenig, Karl; Crijns, Tom J
Health organizations want to measure patient-reported outcome measures (PROMs) longitudinally. Two medical assistants called people selectively at 6 weeks and routinely at 6 months to obtain PROMs as part of routine musculoskeletal specialty care. Only 47% of patients (123 of 263) were reached by phone at 6 weeks and 41% (246 of 594) at 6 months. Spanish speakers were more likely to answer. Eighty-nine percent of people reached at 6 weeks and 76% reached at 6 months were willing to complete PROMs. Speaking Spanish, older age, and fewer symptoms of depression were associated with completing PROMs when reached by phone at 6 weeks. Women and Spanish-speaking patients were more likely to participate at 6 months. The observation that most people do not participate in longitudinal PROM measurement in a system that devotes notable resources in the setting of musculoskeletal specialty care—with some variation by psychosocial factors—suggests that longitudinal PROM measurement may be infeasible. Future work can explore alternative measures of the value of care that account for the large percentage of people that deprioritize care after a single specialty visit.